2022
DOI: 10.1109/access.2022.3145980
|View full text |Cite
|
Sign up to set email alerts
|

Automatic Micro-Crack Detection of Polycrystalline Solar Cells in Industrial Scene

Abstract: Solar energy can be a clean and renewable alternative to traditional fuels, which enables its wide application in our life and the industry. However, some defects inevitably occur in the solar cells during production, transportation, and installation, which will reduce the power generation efficiency. In this paper, we propose a ResNet-based micro-crack detection method to detect the micro-cracks on polycrystalline solar cells. Specifically, a novel feature fusion model is introduced to aggregate the low-level… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…On the other hand, the average accuracy reached 99.23% by using transfer learning method to train the model. Fan et al [ 5 ], aiming at the micro-crack defect target of polycrystalline silicon solar cells, proposed a detection method that enhanced the micro-crack defect feature through image preprocessing and used ResNet50 network as the backbone network to extract the defect feature. Through testing the industrial micro-crack defect dataset, it was found that the detection accuracy rate of this method could reach 98.29%.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, the average accuracy reached 99.23% by using transfer learning method to train the model. Fan et al [ 5 ], aiming at the micro-crack defect target of polycrystalline silicon solar cells, proposed a detection method that enhanced the micro-crack defect feature through image preprocessing and used ResNet50 network as the backbone network to extract the defect feature. Through testing the industrial micro-crack defect dataset, it was found that the detection accuracy rate of this method could reach 98.29%.…”
Section: Introductionmentioning
confidence: 99%
“…Yu et al [ 12 ] proposed a different crack detection method based on image by using deep convolutional neural network and Enhanced Chicken Swarm Algorithm (ECSA), and conducted comparative experiments with other crack detection methods on a variety of concrete crack samples. Fan et al [ 13 ] proposed a microcrack detection method based on ResNet to detect microcracks on polycrystalline solar cells, which effectively improved the accuracy of detecting solar-cell defects. In 2021, on the basis of the U-Net [ 14 ] model, Li et al [ 15 ] used asymmetric convolution to enhance the feature representation and feature extraction capability of the convolution layer, and effectively improved the problem of insufficient feature utilization of the U-Net model.…”
Section: Introductionmentioning
confidence: 99%
“…Tang et al [ 29 ] proposed an evolutionary algorithm which combines traditional image processing techniques, deep learning, migration learning and deep clustering; this fine-tuned model can detect new defects with high accuracy. Fan et al [ 30 ] proposed a migration learning and ResNet-based microcrack detection method, which combines feature fusion and incorporates a self-attention mechanism to aggregate low-level features and deep semantic strong features to significantly improve defect detection.…”
Section: Introductionmentioning
confidence: 99%